Evaluation of patient response and recurrence of pigmentation following gingival depigmentation using laser and scalpel technique: A clinical study - Harpreet Singh Grover; Himanshu Dadlani; Amit Bhardwaj; Anil Yadav; Sanjay Lal (Wolters Kluwer Medknow Publications, 2014)
Aim: The present study was undertaken to evaluate patient response and recurrence of pigmentation following gingival depigmentation carried out with a surgical blade and diode laser. Materials and Methods: Twenty patients who were esthetically conscious of their dark gums and requested treatment for the same were selected for this study. Complete phase I therapy was performed for all the patients before performing the gingival depigmentation procedures with laser and scalpel on a split-mouth basis. Patients were evaluated for pain (1 day, 1 week), wound healing and melanin repigmentation (Melanin Pigmentation Index) immediately and at 1 week, 1 month and 3 months, respectively. Results: The final results were statistically analyzed and significance was evaluated. The results of this study indicated that both scalpel and laser were efficient for gingival depigmentation. Comparative pain assessment (P = 0.148) and repigmentation scores (P = 0.288) at various time intervals between the two groups did not show any statistical significance. Conclusion: Both the procedures did not result in any post-operative complications and the gingiva healed uneventfully. When compared, both the techniques were found to be equally efficacious. Care must be taken to assess the gingival biotype and the degree of pigmentation in deciding which technique is to be used. Clinical Significance: Various methods of depigmentation are available with comparable efficacies. Depigmentation is not a clinical indication but a treatment of choice where esthetics is a concern and is desired by the patient.